Determinants of Strategic Taxpayer Satisfaction and Their Impact on Tax Payment Compliance - Hasnan Iskandar; Luh Putu Mahyuni (Universitas Warmadewa, 2025)
This research was conducted to examine the role of service dimensions in the form of reliability, responsiveness, assurance, empathy and physical form in measuring satisfaction and determine their impact on the level of tax payment compliance. The research was carried out in the working area of the South Badung Pratama Tax Service Office with a population of 523 registered strategic taxpayers. The simple random-sampling method was used in this research by calculating a sample of 127 strategic taxpayers. The research was carried out using the SEM-PLS approach by collecting empirical data through a 10-point Likert scale questionnaire. The research results prove that customer satisfaction can be created through providing services in the form of reliability, responsiveness, assurance, empathy and good physical appearance. An interesting finding in this study is that although reliability is the most dominant factor that can increase strategic taxpayer satisfaction, responsiveness cannot necessarily increase strategic taxpayer satisfaction. Furthermore, this research proves that a high level of strategic taxpayer satisfaction can directly have an impact on increasing tax payment compliance. This study makes a positive contribution to the literature and to the Directorate General of Taxes, especially KPP Pratama South Badung in improving service and satisfaction of strategic taxpayers through reliability, responsiveness, assurance and good empathy and adequate physical form.